2021
DOI: 10.3390/app11052293
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hysteresis Based PWM Schemes ΔΣ-PWM and Direct Torque Control

Abstract: This paper presents the differences and similarities of ΔΣ-PWM as a hysteresis-based PWM scheme with direct torque control (DTC) using simulation models. The variable switching frequency caused by the hysteresis element is examined with regard to its instantaneous values. The comparison is based on an equal maximum switching frequency as a design criterion. With this first assumption, the variation of the instantaneous switching frequency is higher when using DTC because of the temporary prioritization of one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In order to improve the performance of the conventional DFTC technique, the standard hysteresis comparators will be replaced by two TOSMC methods and the switching table by the SVM technique. The rotor flux and electromagnetic torque estimation block maintain the same shape as that established for classical DFTC, as described in [31,32]. In this DFTC control strategy, the rotor flux and torque are regulated by two proposed TOSMC regulators, while the SVM technique replaces the traditional switching table.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the performance of the conventional DFTC technique, the standard hysteresis comparators will be replaced by two TOSMC methods and the switching table by the SVM technique. The rotor flux and electromagnetic torque estimation block maintain the same shape as that established for classical DFTC, as described in [31,32]. In this DFTC control strategy, the rotor flux and torque are regulated by two proposed TOSMC regulators, while the SVM technique replaces the traditional switching table.…”
Section: Introductionmentioning
confidence: 99%
“…This property allows the state trajectory x(t) to converge to a reference trajectory x ref (t) by an appropriate switching between these subsystems. In the first part of this paper, it was shown that the presented approach minimizes the quality functions h s (x(t),x ref (t)) for all s ∈ S by applying the switching law (10). Furthermore, it was shown that reaching the minimumĥ is equivalent to the convergence of the state trajectory x(t) to the reference trajectory x ref (t).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, in [5], it was shown that a hysteresis current control is an effective way of achieving fast dynamic response. For this reason, the design and analysis of different hysteresis current controllers are the subject of many ongoing scientific works [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%